Ablation Rates of Taylor Glacier, Antarctica - Cuffey, Kurt M.; Bliss, Andrew; Kavanaugh, Jeffrey (IEDA: US Antarctic Program Data Center, 2007)
Abstract: This data set provides glacier surface ablation rates for a network of approximately 250 sites on Taylor Glacier, spanning a period from 2003 to 2011. Here sublimation is the dominant ablation mechanism, though a few sites have accumulation. Ablation data are provided in meters water equivalent per year. Data are available via FTP in space-delimited ASCII format.